Effect of Washed Sunflower Oil on Lipid Profile in the Experimental Hypercholesterolemia in the Adult Male Rats - Khalid H. H. Sharaf; Man S. Kalo (College of Education for Pure Sciences, 2009)
Abstract Vegetable oils are considered to be active in modulation of the blood lipid profile and profilacting from cardiovascular diseases, oils extracted from plants (sunflower seeds) may also contains some polar substances which can interferes with their action, if these oils are exposed to some washing processes with worm water, these substances will be removed. A thirty adult albino male rats were divided into five groups and exposed to a hyperlipidemic and hypercholesterolemic diet (animal fats 16% of total calories) and H2O2 (0.5%) in the water for a 30 days for induction of hypercholesterolemia in addition to 15 days in which. sunflower oil are administered orally as a crude and washed oils at a doses of 300 and 600 mg/ kg body weight. There was no significant effect of the washing process on the nutritional status but there were a decrease in total cholesterol TC (50 %), phospholipids PL (42%), low density lipoproteins LDL-c (74%) and elevation in high density lipoproteins HDL-c (70%) resulted from the treatment with washed oil (600 mg/ kg body weight) in addition to decrease in liver malondialdehyde (MDA) content. In conclusion, the washing process of sunflower oil will improve it's hypocholesterolemic and antioxidant effects.